CLINICAL EVALUATION OF ORTHODONTIC PATIENTS BEFORE AND AFTER THE PLACEMENT OF FIXED APPLIANCES - Ioana-Andreea Sioustis; Maria-Alexandra Martu; Ionut Luchian; Irina-Georgeta Sufaru; Liliana Pasarin; Bogdan Vasiliu; Diana-Cristala Kapp; Alexandru Flondor; Sorina-Mihaela Solomon (Romanian Dental Association for Education, 2020)
This study highlights the importance of regular periodontal control in orthodontics. Fix orthodontic treatment impairs a good hygiene and could lead to several complications. Materials and methods. In this study enrolled 20 subjects that met the inclusion and exclusion criteria. The informed consent was signed by all the patients. Results and Discussion. Bleeding on probing and hygiene were assessed before the placement of fixed orthodontic appliances and after. Comparing the values, we found that BOP values increased after placement of fixed orthodontic appliances. Hygiene was not found to be in an optimal level. Conclusions. The results found emphasize the need of regular periodontal control in order to detect and prevent any periodontal issues that could influence the periodontal status.